2003
DOI: 10.1128/jcm.41.8.3514-3520.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Interspersed Repetitive Unit Typing ofMycobacterium tuberculosisCompared to IS6110-Based Restriction Fragment Length Polymorphism Analysis for Investigation of Apparently Clustered Cases of Tuberculosis

Abstract: An evaluation of the utility of IS6110-based restriction fragment length polymorphism (RFLP) typing compared to a combination of variable number tandem repeat (VNTR) typing and mycobacterial interspersed repetitive unit (MIRU) typing was undertaken. A total of 53 patient isolates of Mycobacterium tuberculosis from four presumed episodes of cross-infection were examined. Genomic DNA was extracted from the isolates by a cetyl trimethylammonium bromide method. The number of copies of tandem repeats of the five lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
5
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 38 publications
3
48
5
2
Order By: Relevance
“…We found that spoligotyping missed two IS6110-identical pairs and that MIRU-VNTR typing failed to detect about half of the IS6110-identical matches. These results concur with observations about spoligotyping (6, 7) but appear to contrast with earlier reports about MIRU-VNTR, which suggested that patterns are generally identical within epidemiologically linked clusters (8). On further examination, we noted that for the discordant pairs, most IS6110-defined clusters had only one MIRU-VNTR locus difference between them, and spoligotypes were either identical or differed by one spacer.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…We found that spoligotyping missed two IS6110-identical pairs and that MIRU-VNTR typing failed to detect about half of the IS6110-identical matches. These results concur with observations about spoligotyping (6, 7) but appear to contrast with earlier reports about MIRU-VNTR, which suggested that patterns are generally identical within epidemiologically linked clusters (8). On further examination, we noted that for the discordant pairs, most IS6110-defined clusters had only one MIRU-VNTR locus difference between them, and spoligotypes were either identical or differed by one spacer.…”
Section: Discussioncontrasting
confidence: 57%
“…The major advantage of rapid typing of isolates is the capacity to immediately provide a strain designation, which in turn may facilitate prompt public health intervention. While the technical feasibility of these methods has been well demonstrated (12,26), their public health utility remains to be determined.To date, studies of small outbreaks have shown that results from spoligotyping and MIRU-VNTR typing are often identical among isolates clustered by IS6110-based RFLP (6,7,8,11,15,16,18,23). However, the capacity of these modalities to provide unique patterns among unrelated isolates (i.e., their specificities) in a population-based study has not yet been evaluated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This property is likely due to the selection of short-term and long-term markers among the genes targeted in the multiplex reaction. These targets conferred a high resolution power, as reported for other bacterial species (14,29,39); reliability for the analysis of strains from outbreaks (14); and also reliability for examination of the phylogeny of geographically and temporally separated strains (35). Our results and those obtained by others suggest that the evolutionary frequency of VNTR-containing genes is also adapted to the study of transmission events.…”
Section: Discussionsupporting
confidence: 60%
“…An analysis of different groups of epidemiologically linked M. tuberculosis isolates has indicated that the stability of the MIRU-VNTR loci is adequate for the tracking of outbreak episodes, identification of laboratory cross-contamination, and discrimination between relapses and reinfections (12,18,23).…”
mentioning
confidence: 99%